1979
DOI: 10.1007/bf00426033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dopamine and noradrenaline blockade on amphetamine-induced behaviour in the marmoset

Abstract: Acute administration of 4 mg/kg d-amphetamine in the marmoset results in a large increase in small head movements (checking), an almost total suppression of purposeful activities and social interaction, but little change in the amount of locomotion. Checking behaviour is blocked in a dose dependent manner by 0.03--0.18 mg/kg haloperidol but not by propranolol, aceperone or diazepam, suggesting dopaminergic mediation of this behaviour. The loss of activities and social interaction after amphetamine is not antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…These results are similar to previous reports that HAL decreased social behavior of marmosets (Scraggs et al, 1979) and of rats (Corbett et al, 1993). Since intact myelin sheath in the brain is essential to normal SI as discussed above, it is plausible to speculate that chronic administration of HAL might, by itself, have adverse effects on white matter.…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to previous reports that HAL decreased social behavior of marmosets (Scraggs et al, 1979) and of rats (Corbett et al, 1993). Since intact myelin sheath in the brain is essential to normal SI as discussed above, it is plausible to speculate that chronic administration of HAL might, by itself, have adverse effects on white matter.…”
Section: Discussionsupporting
confidence: 93%
“…Pharmacological and lesion studies provide evidence for a substantial role of dopamine in the locomotor-activating, reinforcing, and stereotypy-inducing actions of AMPH-like stimulants. Although NE does not appear to participate prominently in AMPH-induced stereotypy and AMPH self-administration (Creese and Iversen 1975;Iversen et al 1975;Kelly et al 1975;Kelly and Iversen 1976;Scraggs and Ridley 1979;Delfs and Kelley 1990), impairment of NE neurotransmission does attenuate AMPH-induced hypermotility (Kokkinidis and Anisman 1979;Scraggs and Ridley 1979;Tyler and Tesel 1980;Ogren et al 1988;Mavridis et al 1991). In vivo microdialysis studies of NE release provide results consistent with these observations: AMPH-induced increases in NE release follow more closely changes in locomotor activity than stereotypy (Kuczenski et al 1995).…”
Section: Discussionsupporting
confidence: 51%
“…The combined actions of noradrenergic β-and either α 1 -receptors and/or other neurotransmitter systems may explain the lack of sedative effects of the β-antagonist, propranolol, on cocaine-induced locomotion (Harris et al 1996). Alternatively, because propranolol has been demonstrated to attenuate the locomotor activating effects of AMPH, at least under some conditions (Scraggs and Ridley 1979), the cocaine-induced locomotion and/or arousal may involve mechanisms that differ, in part, from those of AMPH.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have demonstrated that AMPH in primates can induce social withdrawal and isolation (e.g., Scaggs and Ridley 1979;Schiörring 1997;Miczek et al 1981;Nielsen et al 1983) although negative findings have also been reported (Sams-Dodd and Newman 1997). For example, Schiörring (1997) have reported that even very low doses of AMPH can disrupt the motherinfant bond for several hours in green velvet monkeys, and Ellenbroek et al (1989) have used AMPH-induced social withdrawal for the evaluation of potential antipsychotic compounds.…”
Section: Discussionmentioning
confidence: 99%